The cross-sectional relations of COVID-19 fear and stress to psychologica distress among frontline healthcare workers in Selangor, Malaysia - Subhas, Natasha; Pang, Nicholas Tze Ping; Chua, Wei Cheng; Kamu, Assis; Chong, Mun Ho; David, Isabel Shamini; Wei, William Liang Goh; Gunasegaran, Yogaraja Indran; Tan, Kit-Aun (MDPI AG, 2021)
Previous pandemics have demonstrated short and long-term impacts on healthcare workers’ mental health, causing knock-on effects on patient care and professional functioning. Indeed, the present COVID-19 pandemic has created unprecedented disruption in social interactions and working conditions. Malaysia has been under the Recovery Movement Control Order since June 2020; however, with the upsurge of cases, healthcare workers face pressure not only from working in resource-deprived settings but also from the increasing patient load. The primary objective of the present study was to examine the cross-sectional relationship of COVID-19 fear and stress to psychological distress (operationalized as anxiety and depression) in healthcare workers. The present sample included 286 frontline healthcare workers from three hospitals in Selangor, Malaysia. Self-administered questionnaires containing sociodemographic and occupational items, the Malay versions of the Coronavirus Stress Measure scale, the Fear of Coronavirus-19 scale, the Generalized Anxiety Disorder-7, and the Patient Health Questionnaire-9 were distributed via online platforms. Hierarchical multiple regression findings suggest that age, shift work, and COVID-19 stress consistently predicted anxiety and depression among frontline healthcare workers after adjusting for sociodemographic and occupational variables. The present findings suggest that frontline healthcare workers are not only inoculated against COVID-19 itself but also against the psychological sequelae of the pandemic.